Analysis Of The Relationship Of Warm-Up To Core Training Sessions In Age Group III Swimming Athletes - Susanti, Ella; Yohanes; Rubiyatno (CV Media Inti Teknologi, 2025)
This study aims to analyze and find the relationship between warm-up and core training sessions in age group III swimming athletes. The research method used is the qualitative method. The research scene is a training session that is the main source of information, and the data sources are 2 coaches and 8 athletes from Jaya Kapuas Swimming Club and Bintang Khatulistiwa Swimmer Team in Pontianak city, with a total of 1 male athlete and 7 female athletes. The research instruments used were interviews, observation, documentation, and field notes. The data analysis technique used was descriptive qualitative. The results of this study are based on the results of data analysis of indicators of distance, force, and volume of exercise associated with expert recommendations, on average the warm-up session is categorized as less, and the core exercise is categorized as more. Specifically, the results of the triangulation of force indicators in both sessions show that each training component affects the training process, so it can be concluded that there is a relationship between warm-up and core training. The relationship between the warm-up session and this training session performed on swimming athletes can be seen from the comparison of distance and style indicators in each session